FORMATION OF ETHNODEMOGRAPHIC COMPOSITION OF POST-SOVIET KAZAKHSTAN AND INTERNATIONAL AGREEMENT - Maulen Aiganym Bakytbekkyzy,; Karabayeva Zapihan Mukhtarovna,; Bildebaeva Aigul Bakkozhaevna, (Scientific Journal of Pedagogy and Economics, 2021)
The article discusses the description of the history of the ethnic composition of Kazakhstan. A large cycle of materials is based on the data from population censuses and materials of Kazakhstani researchers. A special study of the ethno-demographic growth of post-Soviet Kazakhstan was carried out. Ethno-demographic growth is divided into periods based on history. The arrival of many peoples in Kazakhstan and their history, political decisions of independent Kazakhstan on the way to interethnic harmony are considered. The emergence of ethnic groups in Kazakhstan is a great political event. The decline of the Kazakh population and the increase in the number of representatives of other nationalities have led to a change in the ethnodemography of Kazakhstan. The country has created a unique and effective mechanism for implementing national policy, interethnic and interreligious dialogue through the Assembly of the People of Kazakhstan. Special attention is paid to the description of the activities of the Assembly of the People of Kazakhstan. The Institute has come to the conclusion that it ensures the revival of ethnic identity and culture, forms a single political, legal and cultural platform for ethnic processes and contributes to the preservation of peace and harmony in the country. In general, thanks to the work of the Assembly in our country there is a unique model of interethnic and interfaith harmony, a special atmosphere of trust, solidarity, mutual understanding, where every citizen, regardless of nationality and religion, can fully enjoy the civil rights and freedoms guaranteed by the Constitution, all necessary conditions for the development of traditions. It was noted that the activities of the Assembly contribute to increasing the international prestige of Kazakhstan as a country that effectively solves issues of interethnic relations.